Strapdown inertial navigation system based on micromechanical sensors as a part of tank guided missiles - N.N. Borisov; M.Yu. Solodukhin; A.I. Godunov (Известия высших учебных заведений. Поволжский регион:Технические науки)
Backgroud. The implementation of automatic target capture on the trajectory and the subsequent transition to homing in tank guided missiles is one of the most urgent tasks aimed at increasing the range and accuracy of firing of guided weapons of the tank, which, in this case, is achieved not due to increasing the energy of the gun, but due to technical solutions invested in the design of the missile and onboard equipment of the tank. The use of free-form inertial navigation systems in tank guided missiles to solve guidance tasks will ensure the capture of the target before the launch of the rocket at the required ranges. The purpose is to estimate the effect of errors in measuring the coordinates of a guided missile using a free-form inertial navigation system during the guidance process on the final result using a statistical model of the dynamics of the guided missile with a free-form inertial navigation system as part of the control system. Materials and methods. The article discloses the structure of a statistical model of a guided rocket with a free-form inertial navigation system. The initial data is shown. The impact of statistical characteristics of primary information sensors on the accuracy of the free-form inertial navigation system was assessed. Results. The results of the simulation are given. The effectiveness of introducing a free-form inertial navigation system into the guided missile is shown, which realize the ability to ensure the capture of the target before the launch of the rocket. Conclusions. The use of a statistical model of the dynamics of a guided missile with a freeform inertial navigation system as part of the control system showed that the maximum spatial error of the free-form inertial navigation system in range is realized at “not zero” of the linear acceleration sensor and is 110 m (1.7% of the flight range), and “not zero” of the angular velocity sensor gives an error of 57m (0.9%).